Efektifitas Larutan ZnSO4 33% dan Sukrosa 33% Pada Pemeriksaan Soil Transmitted Helminth Menggunakan Metode Flotasi Sentrifugasi - Nikmatullah, Nurul Azmah (Universitas Muhammadiyah Surabaya, 2023)
Soil-Transmitted Helminth (STH) infection is an infection caused by Ascaris lumbricoides worms, Ancylostoma duodenale worms, Necator americanus worms, and Trichuris trichiura worms. Transmission of infection occurs through soil media containing feces contaminated with STH worm eggs. STH worm infection can be identified by qualitative and semi-quantitative stool examination. Stool qualitative examination consists of the direct slide method (native), the flotation method, and the sedimentation method. This study aims to see the effectiveness of 33% ZnSO4 solution and 33% sucrose solution in examining STH worm eggs in the centrifugation flotation method. This study began by collecting feces samples; then the samples were identified by using the flotation centrifugation method. The solutions used in this method were 33% ZnSO4 solution and 33% sucrose solution. The data obtained were analyzed by using the Mann-Whitney test. There were 35 stool samples identified. The examination results obtained 13 positive samples of Ascaris lumbricoides worm eggs in 33% ZnSO4 solution and 1 positive sample in 33% sucrose solution, and the results of the Mann Whitney test obtained Asymp. Sig <0.05. Therefore, there is a significant difference between the 33% ZnSO4 solution and the 33% sucrose solution. In conclusion, the most effective solution used in the flotation method is 33% ZnSO4. Keywords: Soil-Transmitted Helminth Infection, Centrifugation Flotation, 33% ZnSO4 Solution, 33% Sucrose Solution